Relation of Student-Teacher Trust with School Well-Being to High School Students - Meilisa Petrisya Hongwidjojo; Monika Monika; Erik Wijaya (PSIKODIMENSIA, 2018)
This research is a correlational study using quantitative method of distributing questionnaires to students of class X, XI and XII in X Senior High School in the area of West Jakarta and Y Senior High School in North Jakarta. Student-teacher trust questionnaire refers to Tchannen-Moran’s study, while school well-being questionnaire refers to Konu and Rimpelä’s study. The research is using purposive sampling technique involving 486 students. The results of the study shows that student-teacher trust has a significant positive relationship with school well-being, so that the higher student-teacher trust, the higher the school well-being. As additional, this study also shows that there is no significant difference in terms of gender.